Scoring the risk of having systemic mastocytosis in adult patients with mastocytosis in the skin - Fuchs, David; Kilbertus, Alex; Kofler, Karin; von Bubnoff, Nikolas; Shoumariyeh, Khalid; Zanotti, Roberta; Bonadonna, Patrizia; Scaffidi, Luigi; Doubek, Michael; Elberink, Hanneke Oude; Span, Lambert F. R.; Hermine, Olivier; et al. (The journal of allergy and clinical immunology. In practice, 2021)
Background - Mastocytosis in adults often presents with skin lesions. A bone marrow biopsy is necessary to confirm or exclude the presence of systemic mastocytosis (SM) in these cases. When a bone marrow biopsy is not performed, the provisional diagnosis is mastocytosis in the skin (MIS). No generally accepted scoring system has been established to estimate the risk of SM in these patients. - Objective - To develop a risk score to predict SM in adults with MIS. - Methods - We examined 1145 patients with MIS from the European Competence Network on Mastocytosis Registry who underwent a bone marrow biopsy. A total of 944 patients had SM and 201 patients had cutaneous mastocytosis; 63.7% were female, and 36.3% were male. Median age was 44 ± 13.3 years. The median serum tryptase level amounted to 29.3 ± 81.9 ng/mL. We established a multivariate regression model using the whole population of patients as a training and validation set (bootstrapping). A risk score was developed and validated with receiver-operating curves. - Results - In the multivariate model, the tryptase level (P < .001), constitutional/cardiovascular symptoms (P = .014), and bone symptoms/osteoporosis (P < .001) were independent predictors of SM (P < .001; sensitivity, 90.7%; specificity, 69.1%). A 6-point risk score was established (risk, 10.7%-98.0%) and validated. - Conclusions - Using a large data set of the European Competence Network on Mastocytosis Registry, we created a risk score to predict the presence of SM in patients with MIS. Although the score will need further validation in independent cohorts, our score seems to discriminate safely between patients with SM and with pure cutaneous mastocytosis.
Gesehen am 14.07.2021